Faktor-Faktor Yang Mempengaruhi Peringkat Obligasi Pada Perusahaan Keuangan - Catherine Amelia Wijaya, Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study was made with the aim to examine the effect of board size, board independence, leverage and profitability on bonds rating. This study uses 69 data samples from financial companies listed on the Indonesia Stock Exchange from the period of 2016-2018. This study uses Microsoft Office 365 software and IBM SPSS Statistics V25.0 to perform data processing. The results obtained in this study are board size has a positive and significant effect on bonds rating, leverage has a negative and significant effect on bonds rating while board independence and profitability has insignificant influence on bonds rating.